Preparation method and application of oxygen-sulfur-doped porous carbon material for rubber waterstop reinforcement
By using porous carbon materials doped with oxysulfide in the rubber water stop, the problems of uneven sulfur distribution and resource waste are solved, the performance of rubber and sulfur utilization efficiency are improved, and the performance of rubber water stop is achieved. .
Patent Information
- Application Number
- CN202411442890.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-10-16
AI Technical Summary
The uneven distribution of sulfur in the existing rubber water stops leads to uneven cross-linking structure, poor performance, and waste of sulfur resources, making it difficult to improve the rolling resistance and dynamic heat generation performance of rubber.
Using oxosulfur-doped porous carbon material as reinforcement for rubber water stops, oxygen is prepared by mixing biomass materials with sulfur, aliphatic diamines and polyvinyl chloride under specific conditions, and ball milling and carbonization treatment. Sulfur-doped porous carbon material used to improve the physical and chemical properties of rubber.
It significantly improves the tear strength and dynamic heat generation performance of the rubber water stop, reduces the amount of sulfur used, improves the utilization efficiency of sulfur, improves the distribution uniformity of sulfur, and enhances the overall performance of rubber.
Smart Images

Figure CN118954485B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method and application of an oxygen-sulfur doped porous carbon material used as a rubber waterstop reinforcing agent, and relates to the field of carbon materials. Background Art
[0002] Carbon is one of the most common elements in nature. 3 Hybridization forms a single bond, and can also be sp 2 and sp hybridization to form stable double and triple bonds, thus forming allotropes with very different structures and properties, such as zero-dimensional carbon black and fullerene, one-dimensional carbon nanotubes and carbon nanofibers, two-dimensional graphene, etc. Carbon materials can be added to rubber as fillers to enhance the physical, thermal, electrical and gas / liquid barrier properties of rubber, and reduce the production cost of rubber products.
[0003] Sulfur is also an important additive for rubber processing. Vulcanization can effectively improve the strength, hardness, wear resistance and tensile resistance of rubber products, thereby improving product quality and service life. Vulcanization can also affect the processing properties of rubber, making the rubber have good plasticity and processability. Vulcanization also has a certain impact on the insulation and weather resistance of rubber. It can enhance the weather resistance of rubber and prevent aging. The low solubility of traditional elemental sulfur in the rubber matrix will cause sulfur to migrate to the surface of the rubber matrix and aggregate. The uneven distribution of insoluble sulfur will cause the cross-linking structure of the vulcanized rubber to be uneven and the performance is poor. In addition, the incomplete vulcanization reaction of sulfur particles may result in a considerable proportion of free sulfur residue, which is not conducive to the performance improvement of vulcanized rubber and will also cause a waste of sulfur resources.
[0004] Based on the above background, the applicant has conducted research on oxygen-sulfur doped porous carbon materials with the intention of providing a porous carbon material for use as a rubber waterstop reinforcement. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a preparation method and application of an oxygen-sulfur-doped porous carbon material used as a rubber waterstop reinforcing agent.
[0006] To solve the above problems, the technical solution adopted by the present invention is:
[0007] Technical Theme 1
[0008] The method for preparing an oxygen-sulfur-doped porous carbon material for a rubber waterstop reinforcing agent comprises the following steps:
[0009] S1: Mix the biomass material and the alkali ball mill, and place the ball-milled mixture into alcohol water and stir at room temperature for 2-4 hours;
[0010] S2: Heat sulfur, aliphatic diamine and polyvinyl chloride in distilled water at 40-70°C and reflux with stirring for 6-8 hours;
[0011] S3: Stir polyvinyl alcohol in water at room temperature and dissolve it quickly after heating;
[0012] S4: quickly add the solution obtained in S3 to the product obtained in S1 which is stirred at a constant speed of 470-570 r / min, continue stirring at room temperature for 20-30 min, then add the product obtained in S2 and stir at room temperature for 2.5-3.5 hours. After stirring, freeze-dry the product;
[0013] S5: carbonizing the freeze-dried product of S4 at 700-900° C. under a protective gas atmosphere, washing and filtering after cooling, to obtain an oxygen-sulfur doped porous carbon material;
[0014] The biomass material is selected from one of corn straw powder, wheat straw powder and rice straw powder.
[0015] As a further improvement of the present invention, the mass ratio of the biomass material to the alkali is 5:2.5-3.5;
[0016] The alcohol water is a mixture of ethanol and water in a volume ratio of 1-2:2-1;
[0017] The mass ratio of sulfur, aliphatic diamine and polyvinyl chloride is 3:2.5-3.5:4-6;
[0018] The base is selected from any one or more of sodium hydroxide, potassium hydroxide, and sodium carbonate;
[0019] The aliphatic diamine is selected from one of 1,3-propylenediamine, ethylenediamine and 1,2-propylenediamine;
[0020] The protective gas is selected from one of nitrogen, helium and argon;
[0021] The mass ratio of the biomass material to sulfur is 1:0.8-1.2;
[0022] The mass ratio of the biomass material to polyvinyl alcohol is 1:0.8-1.2.
[0023] As a further improvement of the present invention, the rotation speed of the ball mill in step S1 is 600-700 r / min, the ball milling is performed for 15-25 min, and then the process is paused for 5-10 min, and the process is repeated 3-5 times.
[0024] As a further improvement of the present invention, in the carbonization process in step S5, protective gas is continuously introduced at a rate of 20-35 mL / min, the temperature is increased from room temperature to 300-400°C at a rate of 2-4°C / min, and the temperature is kept at 300-400°C for 40-80 minutes, and then the temperature is further increased to 700-900°C at a rate of 3-10°C / min. After being kept at 700-900°C for 60-180 minutes, the temperature is then reduced to 400-600°C at a rate of 3-10°C / min, and finally the temperature is naturally reduced from 400-600°C to room temperature.
[0025] As a further improvement of the present invention, the mass ratio of the biomass material to the alkali is 5:3;
[0026] The mass ratio of sulfur, aliphatic diamine and polyvinyl chloride is 3:3:5, the heating reflux stirring time is 7 hours, and the temperature is 50°C;
[0027] The biomass material is corn stalk powder;
[0028] The alcohol water is a mixture of ethanol and water in a volume ratio of 1:1;
[0029] The base is selected from sodium hydroxide and potassium hydroxide in a mass ratio of 1:1;
[0030] The aliphatic diamine is selected from 1,3-propylenediamine;
[0031] The mass ratio of the biomass material to the polyvinyl alcohol is 1:1;
[0032] The mass ratio of the biomass material to sulfur is 1:0.9.
[0033] As a further improvement of the present invention, the rotation speed of the ball mill in step S1 is 650 rpm, the ball milling is performed for 20 min, and then the ball milling is paused for 10 min, which is repeated 4 times.
[0034] As a further improvement of the present invention, during the carbonization process in step S5, protective gas is continuously introduced at a rate of 28 mL / min, the temperature is increased from room temperature to 350°C at a rate of 3°C / min, kept at 350°C for 60 minutes, then increased from 350°C to 800°C at a rate of 5°C / min, kept at 800°C for 120 minutes, then cooled to 500°C at a rate of 5°C / min, and finally naturally cooled from 500°C to room temperature.
[0035] Technical Theme 2
[0036] An oxygen-sulfur-doped porous carbon material used as a rubber waterstop reinforcement obtained by the preparation method provided in Technical Topic 1.
[0037] Technical Theme 3
[0038] An application of an oxygen-sulfur-doped porous carbon material used as a rubber waterstop reinforcement agent obtained by the preparation method provided in Technical Topic 1 in the field of rubber preparation.
[0039] In some embodiments of the present invention, the application is the preparation of a rubber waterstop.
[0040] The beneficial effects of adopting the above technical solution are:
[0041] 1. Oxygen-doped carbon materials can greatly improve their rolling resistance and dynamic heat generation, enhance their interaction with natural rubber, improve their dispersibility in the rubber matrix, and at the same time improve the tear strength of the rubber waterstop.
[0042] 2. Polyvinyl alcohol is rich in hydroxyl groups and has unsaturated bonds, which is a raw material binder. It promotes the binding between biomass materials or between biomass materials and other additives, and improves the yield after carbonization.
[0043] 3. At a mild temperature of 50°C, aliphatic diamines promote the ring-opening polymerization of elemental sulfur on polyvinyl chloride. The active sulfur sites on polyvinyl chloride are beneficial to improving the performance of rubber products and reducing the amount of sulfur used in the preparation of rubber waterstops. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 This is the XPS spectrum of sulfur in the oxygen-sulfur doped porous carbon material prepared in Example 1 of the present invention.
[0045] Figure 2 This is the XPS spectrum of oxygen of the oxygen-sulfur doped porous carbon material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0046] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention is clearly and completely described below in conjunction with specific embodiments.
[0047] The numbers mentioned in the experimental examples, comparative examples and effect examples are all by mass.
[0048] Example 1
[0049] S1: 3 parts of corn straw powder and 1.8 parts of a mixed alkali of KOH and NaOH in a mass ratio of 1:1 were mixed and ball-milled (ball milling speed of 650 rpm, ball milling for 20 minutes and pause for 10 minutes, repeated four times), and then placed in a mixed solvent of 90 parts of ethanol and water (ethanol and water volume ratio of 1:1) at room temperature and stirred for 3 hours to obtain A;
[0050] S2: 2.7 parts of sulfur, 2.7 parts of 1,3-propylenediamine, and 4.5 parts of polyvinyl chloride were placed in 63 parts of distilled water and heated under reflux at 50°C for 7 hours to obtain B;
[0051] S3: Take 3 parts of polyvinyl alcohol and place them in 30 parts of distilled water, stir them evenly at room temperature, and then quickly heat them to 90-95°C to dissolve them quickly to obtain C;
[0052] S4: The solution obtained in S3 is quickly added to the product obtained in S1 which is stirred at a constant speed of 520 r / min, and stirred at room temperature for 25 min. Then, the product obtained in S2 is added thereto and stirred at room temperature for 3 hours. After the stirring is completed, the product is freeze-dried;
[0053] S5: The freeze-dried product of S4 was subjected to high-temperature carbonization treatment. During the process, nitrogen was continuously introduced at a rate of 28 mL / min, the temperature was increased from room temperature to 350°C at a rate of 3°C / min, and the temperature was kept at 350°C for 60 minutes. The temperature was then increased from 350°C to 800°C at a rate of 5°C / min. After being kept at 800°C for 120 minutes, the temperature was then decreased to 500°C at a rate of 5°C / min. Finally, the temperature was naturally decreased from 500°C to room temperature to obtain a black semi-finished product. The black semi-finished product was filtered and washed with distilled water for 3 times, and then dried to obtain an oxygen-sulfur doped porous carbon material.
[0054] Example 2
[0055] S1: 3 parts of wheat straw powder and 1.8 parts of a mixed alkali of KOH and NaOH in a mass ratio of 1:1 were mixed and ball-milled (ball milling speed was 650 rpm, ball milling was stopped for 10 minutes after 20 minutes, and repeated four times), and then placed in a mixed solvent of 90 parts of ethanol and water (ethanol and water volume ratio was 1:1) and stirred at room temperature for 3 hours to obtain A;
[0056] S2: 2.7 parts of sulfur, 2.7 parts of ethylenediamine, and 4.5 parts of polyvinyl chloride were placed in 63 parts of distilled water and heated under reflux at 50°C with stirring for 7 hours to obtain B;
[0057] S3: Take 3 parts of polyvinyl alcohol and place them in 30 parts of distilled water, stir them evenly at room temperature, and then quickly heat them to 90-95°C to dissolve them quickly to obtain C;
[0058] S4: The solution obtained in S3 is quickly added to the product obtained in S1 which is stirred at a constant speed of 520 r / min, and stirred at room temperature for 25 min. Then, the product obtained in S2 is added thereto and stirred at room temperature for 3 hours. After the stirring is completed, the product is freeze-dried;
[0059] S5: During the high-temperature carbonization treatment of the freeze-dried product of S4, nitrogen was continuously introduced at a rate of 28 mL / min, the temperature was increased from room temperature to 350°C at a rate of 3°C / min, and the temperature was kept at 350°C for 60 minutes. The temperature was then increased from 350°C to 800°C at a rate of 5°C / min. After keeping at 800°C for 120 minutes, the temperature was then decreased to 500°C at a rate of 5°C / min. Finally, the temperature was naturally decreased from 500°C to room temperature to obtain a black semi-finished product. The black semi-finished product was filtered and washed with distilled water for 3 times, and then dried to obtain an oxygen-sulfur doped porous carbon material.
[0060] Example 3
[0061] S1: 3 parts of corn straw powder and 1.5 parts of a mixed alkali of KOH and NaOH in a mass ratio of 1:1 were mixed and ball-milled (ball milling speed was 650 rpm, ball milling was stopped for 10 minutes after 20 minutes, and repeated four times), and then placed in a mixed solvent of 90 parts of ethanol and water (ethanol and water volume ratio was 1:1) and stirred at room temperature for 3 hours to obtain A;
[0062] S2: 2.7 parts of sulfur, 2.25 parts of 1,3-propylenediamine, and 3.6 parts of polyvinyl chloride were placed in 63 parts of distilled water and heated under reflux at 50°C for 7 hours to obtain B;
[0063] S3: Take 3 parts of polyvinyl alcohol and place them in 30 parts of distilled water, stir them evenly at room temperature, and then quickly heat them to 90-95°C to dissolve them quickly to obtain C;
[0064] S4: The solution obtained in S3 is quickly added to the product obtained in S1 which is stirred at a constant speed of 520 r / min, and stirred at room temperature for 25 min. Then, the product obtained in S2 is added thereto and stirred at room temperature for 3 hours. After the stirring is completed, the product is freeze-dried;
[0065] S5: During the high-temperature carbonization treatment of the freeze-dried product of S4, nitrogen was continuously introduced at a rate of 28 mL / min, the temperature was increased from room temperature to 350°C at a rate of 3°C / min, and the temperature was kept at 350°C for 60 minutes. The temperature was then increased from 350°C to 800°C at a rate of 5°C / min. After keeping at 800°C for 120 minutes, the temperature was then decreased to 500°C at a rate of 5°C / min. Finally, the temperature was naturally decreased from 500°C to room temperature to obtain a black semi-finished product. The black semi-finished product was filtered and washed with distilled water for 3 times, and then dried to obtain an oxygen-sulfur doped porous carbon material.
[0066] Example 4
[0067] S1: 3 parts of corn straw powder and 1.8 parts of a mixed alkali of KOH and NaOH in a mass ratio of 1:1 were ball-milled (ball milling speed of 650 rpm, ball milling for 25 minutes and pause for ten minutes, repeated three times), and then placed in a mixed solvent of 90 parts of ethanol and water (ethanol and water volume ratio of 1:1) at room temperature and stirred for 3 hours to obtain A;
[0068] S2: 2.7 parts of sulfur, 2.7 parts of 1,3-propylenediamine, and 4.5 parts of polyvinyl chloride were placed in 63 parts of distilled water and heated under reflux at 50°C for 7 hours to obtain B;
[0069] S3: 3.6 parts of polyvinyl alcohol are placed in 30 parts of distilled water and stirred at room temperature, and then the temperature is quickly raised to 90-95°C to dissolve quickly to obtain C;
[0070] S4: The solution obtained in S3 is quickly added to the product obtained in S1 which is stirred at a constant speed of 520 r / min, and stirred at room temperature for 25 min. Then, the product obtained in S2 is added thereto and stirred at room temperature for 3 hours. After the stirring is completed, the product is freeze-dried;
[0071] S5: During the high-temperature carbonization treatment of the freeze-dried product of S4, nitrogen was continuously introduced at a rate of 28 mL / min, the temperature was increased from room temperature to 350°C at a rate of 3°C / min, and the temperature was kept at 350°C for 60 minutes. The temperature was then increased from 350°C to 800°C at a rate of 5°C / min. After keeping at 800°C for 120 minutes, the temperature was then decreased to 500°C at a rate of 5°C / min. Finally, the temperature was naturally decreased from 500°C to room temperature to obtain a black semi-finished product. The black semi-finished product was filtered and washed with distilled water for 3 times, and then dried to obtain an oxygen-sulfur doped porous carbon material.
[0072] Example 5
[0073] S1: 3 parts of corn straw powder and 1.8 parts of a mixed alkali of KOH and NaOH in a mass ratio of 1:1 were mixed and ball-milled (ball milling speed of 650 rpm, ball milling for 20 minutes and pause for 10 minutes, repeated four times), and then placed in a mixed solvent of 90 parts of ethanol and water (ethanol and water volume ratio of 1:1) at room temperature and stirred for 3 hours to obtain A;
[0074] S2: 2.7 parts of sulfur, 2.7 parts of 1,3-propylenediamine, and 4.5 parts of polyvinyl chloride were placed in 63 parts of distilled water and heated under reflux at 50°C for 7 hours to obtain B;
[0075] S3: Take 3 parts of polyvinyl alcohol and place them in 30 parts of distilled water, stir them evenly at room temperature, and then quickly heat them to 90-95°C to dissolve them quickly to obtain C;
[0076] S4: The solution obtained in S3 is quickly added to the product obtained in S1 which is stirred at a constant speed of 470 r / min, and stirred at room temperature for 30 min. Then, the product obtained in S2 is added thereto and stirred at room temperature for 2.5 hours. After the stirring is completed, the product is freeze-dried;
[0077] S5: During the high-temperature carbonization treatment of the freeze-dried product of S4, nitrogen was continuously introduced at a rate of 28 mL / min, the temperature was increased from room temperature to 300°C at a rate of 3°C / min, and the temperature was kept at 300°C for 80 minutes. The temperature was then increased from 300°C to 700°C at a rate of 5°C / min. After keeping at 700°C for 180 minutes, the temperature was then decreased to 500°C at a rate of 5°C / min. Finally, the temperature was naturally decreased from 500°C to room temperature to obtain a black semi-finished product. The black semi-finished product was filtered and washed with distilled water for 3 times, and then dried to obtain an oxygen-sulfur doped porous carbon material.
[0078] Example 6
[0079] S1: 3 parts of corn straw powder and 2.1 parts of a mixed alkali of KOH and NaOH in a mass ratio of 1:1 were mixed and ball-milled (ball milling speed of 650 rpm, ball milling for 20 minutes and pause for 10 minutes, repeated four times), and then placed in a mixed solvent of 90 parts of ethanol and water (ethanol and water volume ratio of 1:1) at room temperature and stirred for 3 hours to obtain A;
[0080] S2: 2.4 parts of sulfur, 2.4 parts of 1,3-propylenediamine, and 4 parts of polyvinyl chloride were placed in 63 parts of distilled water and heated under reflux at 50°C with stirring for 7 hours to obtain B;
[0081] S3: Take 2.4 parts of polyvinyl alcohol and place it in 30 parts of distilled water, stir it evenly at room temperature, and then quickly heat it to 90-95°C to dissolve it quickly to obtain C;
[0082] S4: The solution obtained in S3 is quickly added to the product obtained in S1 which is stirred at a constant speed of 520 r / min, and stirred at room temperature for 25 min. Then, the product obtained in S2 is added thereto and stirred at room temperature for 3 hours. After the stirring is completed, the product is freeze-dried;
[0083] S5: During the high-temperature carbonization treatment of the freeze-dried product of S4, nitrogen was continuously introduced at a rate of 28 mL / min, the temperature was increased from room temperature to 350°C at a rate of 3°C / min, and the temperature was kept at 350°C for 60 minutes. The temperature was then increased from 350°C to 800°C at a rate of 5°C / min. After keeping at 800°C for 120 minutes, the temperature was then decreased to 500°C at a rate of 5°C / min. Finally, the temperature was naturally decreased from 500°C to room temperature to obtain a black semi-finished product. The black semi-finished product was filtered and washed with distilled water for 3 times, and then dried to obtain an oxygen-sulfur doped porous carbon material.
[0084] Example 7
[0085] S1: 3 parts of corn stalk powder and 1.8 parts of a mixed alkali of KOH and NaOH in a mass ratio of 1:1 were mixed and ball-milled (ball milling speed was 700 rpm, ball milling was repeated for 15 minutes and then paused for 10 minutes, and repeated five times), and then placed in a mixed solvent of 90 parts of ethanol and water (ethanol and water volume ratio was 1:1) at room temperature and stirred for 3 hours to obtain A;
[0086] S2: 3.6 parts of sulfur, 4.2 parts of 1,3-propylenediamine, and 7.2 parts of polyvinyl chloride were placed in 90 parts of distilled water and heated under reflux at 50°C for 7 hours to obtain B;
[0087] S3: Take 3 parts of polyvinyl alcohol and place them in 30 parts of distilled water, stir them evenly at room temperature, and then quickly heat them to 90-95°C to dissolve them quickly to obtain C;
[0088] S4: The solution obtained in S3 is quickly added to the product obtained in S1 which is stirred at a constant speed of 520 r / min, and stirred at room temperature for 25 min. Then, the product obtained in S2 is added thereto and stirred at room temperature for 3 hours. After the stirring is completed, the product is freeze-dried;
[0089] S5: During the high-temperature carbonization treatment of the freeze-dried product of S4, nitrogen was continuously introduced at a rate of 28 mL / min, the temperature was increased from room temperature to 350°C at a rate of 3°C / min, and the temperature was kept at 350°C for 60 minutes. The temperature was then increased from 350°C to 800°C at a rate of 5°C / min. After keeping at 800°C for 120 minutes, the temperature was then decreased to 500°C at a rate of 5°C / min. Finally, the temperature was naturally decreased from 500°C to room temperature to obtain a black semi-finished product. The black semi-finished product was filtered and washed with distilled water for 3 times, and then dried to obtain an oxygen-sulfur doped porous carbon material.
[0090] Example 8
[0091] S1: 3 parts of corn straw powder and 1.8 parts of a mixed alkali of KOH and NaOH in a mass ratio of 1:1 were mixed and ball-milled (ball milling speed was 600 rpm, ball milling was stopped for 10 minutes after 25 minutes, and repeated four times), and then placed in a mixed solvent of 90 parts of ethanol and water (ethanol and water volume ratio was 1:1) and stirred at room temperature for 3 hours to obtain A;
[0092] S2: 2.7 parts of sulfur, 2.7 parts of 1,3-propylenediamine, and 4.5 parts of polyvinyl chloride were placed in 63 parts of distilled water and heated under reflux at 50°C for 7 hours to obtain B;
[0093] S3: Take 3 parts of polyvinyl alcohol and place them in 30 parts of distilled water, stir them evenly at room temperature, and then quickly heat them to 90-95°C to dissolve them quickly to obtain C;
[0094] S4: The solution obtained in S3 is quickly added to the product obtained in S1 which is stirred at a constant speed of 520 r / min, and stirred at room temperature for 25 min. Then, the product obtained in S2 is added thereto and stirred at room temperature for 3 hours. After the stirring is completed, the product is freeze-dried;
[0095] S5: During the high-temperature carbonization treatment of the freeze-dried product of S4, nitrogen was continuously introduced at a rate of 28 mL / min, the temperature was increased from room temperature to 400°C at a rate of 4°C / min, and it was kept at 400°C for 40 minutes. Then, the temperature was increased from 400°C to 900°C at a rate of 10°C / min. After keeping at 900°C for 60 minutes, the temperature was decreased to 500°C at a rate of 10°C / min, and finally, the temperature was naturally decreased from 500°C to room temperature to obtain a black semi-finished product. The black semi-finished product was filtered and washed with distilled water for 3 times, and then dried to obtain an oxygen-sulfur doped porous carbon material.
[0096] Example 9
[0097] S1: 3 parts of rice straw powder and 1.8 parts of a mixed alkali of KOH and Na2CO3 in a mass ratio of 1:1 were mixed and ball-milled (ball milling speed of 650 rpm, ball milling for 20 minutes and pause for 10 minutes, repeated four times), and then placed in a mixed solvent of 90 parts of ethanol and water (ethanol and water volume ratio of 1:1) at room temperature and stirred for 3 hours to obtain A;
[0098] S2: 2.7 parts of sulfur, 2.7 parts of 1,3-propylenediamine, and 4.5 parts of polyvinyl chloride were placed in 63 parts of distilled water and heated under reflux at 50°C for 7 hours to obtain B;
[0099] S3: Take 3 parts of polyvinyl alcohol and place them in 30 parts of distilled water, stir them evenly at room temperature, and then quickly heat them to 90-95°C to dissolve them quickly to obtain C;
[0100] S4: The solution obtained in S3 is quickly added to the product obtained in S1 which is stirred at a constant speed of 570 r / min, and stirred at room temperature for 20 min. Then, the product obtained in S2 is added thereto and stirred at room temperature for 3.5 hours. After the stirring is completed, the product is freeze-dried;
[0101] S5: During the high-temperature carbonization treatment of the freeze-dried product of S4, nitrogen was continuously introduced at a rate of 28 mL / min, the temperature was increased from room temperature to 350°C at a rate of 3°C / min, and the temperature was kept at 350°C for 60 minutes. The temperature was then increased from 350°C to 800°C at a rate of 5°C / min. After keeping at 800°C for 120 minutes, the temperature was then decreased to 500°C at a rate of 5°C / min. Finally, the temperature was naturally decreased from 500°C to room temperature to obtain a black semi-finished product. The black semi-finished product was filtered and washed with distilled water for 3 times, and then dried to obtain an oxygen-sulfur doped porous carbon material.
[0102] Comparative Example 1
[0103] S1: 3 parts of chitosan and 1.8 parts of a mixed alkali of KOH and NaOH in a mass ratio of 1:1 were mixed and ball-milled (ball milling speed of 650 rpm, ball milling for 20 minutes and pause for 10 minutes, repeated four times), and then placed in a mixed solvent of 90 parts of ethanol and water (ethanol and water volume ratio of 1:1) at room temperature and stirred for 3 hours to obtain A;
[0104] S2: 2.7 parts of sulfur, 2.7 parts of 1,3-propylenediamine, and 4.5 parts of polyvinyl chloride were placed in 63 parts of distilled water and heated under reflux at 50°C for 7 hours to obtain B;
[0105] S3: Take 3 parts of polyvinyl alcohol and place them in 30 parts of distilled water, stir them evenly at room temperature, and then quickly heat them to 90-95°C to dissolve them quickly to obtain C;
[0106] S4: The solution obtained in S3 is quickly added to the product obtained in S1 which is stirred at a constant speed of 520 r / min, and stirred at room temperature for 25 min. Then, the product obtained in S2 is added thereto and stirred at room temperature for 3 hours. After the stirring is completed, the product is freeze-dried;
[0107] S5: During the high-temperature carbonization treatment of the freeze-dried product of S4, nitrogen was continuously introduced at a rate of 28 mL / min, the temperature was increased from room temperature to 350°C at a rate of 3°C / min, and the temperature was kept at 350°C for 60 minutes. The temperature was then increased from 350°C to 800°C at a rate of 5°C / min. After keeping at 800°C for 120 minutes, the temperature was then decreased to 500°C at a rate of 5°C / min. Finally, the temperature was naturally decreased from 500°C to room temperature to obtain a black semi-finished product. The black semi-finished product was filtered and washed with distilled water for 3 times, and then dried to obtain an oxygen-sulfur doped porous carbon material.
[0108] Comparative Example 2
[0109] S1: 3 parts of corn straw powder and 1.8 parts of a mixed alkali of KOH and NaOH in a mass ratio of 1:1 were mixed and ball-milled (ball milling speed of 650 rpm, ball milling for 20 minutes and pause for 10 minutes, repeated four times), and then placed in a mixed solvent of 90 parts of ethanol and water (ethanol and water volume ratio of 1:1) at room temperature and stirred for 3 hours to obtain A;
[0110] S2: 2.7 parts of sulfur, 2.7 parts of 1,3-propylenediamine, and 4.5 parts of polyvinyl chloride were placed in 63 parts of distilled water and heated under reflux at 50°C for 7 hours to obtain B;
[0111] S3: Take 3 parts of polyethylene glycol and place them in 30 parts of distilled water, stir them evenly at room temperature, and then quickly heat them to 90-95°C to dissolve them quickly to obtain C;
[0112] S4: The solution obtained in S3 is quickly added to the product obtained in S1 which is stirred at a constant speed of 520 r / min, and stirred at room temperature for 25 min. Then, the product obtained in S2 is added thereto and stirred at room temperature for 3 hours. After the stirring is completed, the product is freeze-dried;
[0113] S5: During the high-temperature carbonization treatment of the freeze-dried product of S4, nitrogen was continuously introduced at a rate of 28 mL / min, the temperature was increased from room temperature to 350°C at a rate of 3°C / min, and the temperature was kept at 350°C for 60 minutes. The temperature was then increased from 350°C to 800°C at a rate of 5°C / min. After keeping at 800°C for 120 minutes, the temperature was then decreased to 500°C at a rate of 5°C / min. Finally, the temperature was naturally decreased from 500°C to room temperature to obtain a black semi-finished product. The black semi-finished product was filtered and washed with distilled water for 3 times, and then dried to obtain an oxygen-sulfur doped porous carbon material.
[0114] Comparative Example 3
[0115] S1: 3 parts of corn straw powder and 1.8 parts of a mixed alkali of KOH and NaOH in a mass ratio of 1:1 were mixed and ball-milled (ball milling speed of 650 rpm, ball milling for 20 minutes and pause for 10 minutes, repeated four times), and then placed in a mixed solvent of 90 parts of ethanol and water (ethanol and water volume ratio of 1:1) at room temperature and stirred for 3 hours to obtain A;
[0116] S2: 2.7 parts of sulfur, 2.7 parts of 1,3-propylenediamine, and 4.5 parts of polyvinyl chloride were placed in 63 parts of distilled water and heated under reflux at 50°C for 7 hours to obtain B;
[0117] S3: Take 3 parts of polyvinyl alcohol and place them in 30 parts of distilled water, stir them evenly at room temperature, and then quickly heat them to 90-95°C to dissolve them quickly to obtain C;
[0118] S4: The product obtained in S2 is quickly added to the product obtained in S1 which is stirred at a constant speed of 520 r / min, and stirred at room temperature for 25 min. Then, the solution obtained in S3 is added thereto and stirred at room temperature for 3 hours. After the stirring is completed, the product is freeze-dried;
[0119] S5: During the high-temperature carbonization treatment of the freeze-dried product of S4, nitrogen was continuously introduced at a rate of 28 mL / min, the temperature was increased from room temperature to 350°C at a rate of 3°C / min, and the temperature was kept at 350°C for 60 minutes. The temperature was then increased from 350°C to 800°C at a rate of 5°C / min. After keeping at 800°C for 120 minutes, the temperature was then decreased to 500°C at a rate of 5°C / min. Finally, the temperature was naturally decreased from 500°C to room temperature to obtain a black semi-finished product. The black semi-finished product was filtered and washed with distilled water for 3 times, and then dried to obtain an oxygen-sulfur doped porous carbon material.
[0120] Comparative Example 4
[0121] S1: 3 parts of corn stalk powder and 1.8 parts of a mixed alkali of KOH and NaOH in a mass ratio of 1:1 were mixed and ball-milled (ball milling speed was 650 rpm, ball milling was stopped for 10 minutes after 20 minutes, and repeated four times), 3 parts of polyvinyl alcohol were added after ball milling, and then placed in a mixed solvent of 90 parts of ethanol and water (the volume ratio of ethanol to water was 1:1) and stirred at room temperature for 3 hours to obtain A;
[0122] S2: 2.7 parts of sulfur, 2.7 parts of 1,3-propylenediamine, and 4.5 parts of polyvinyl chloride were placed in 63 parts of distilled water and heated under reflux at 50°C for 7 hours to obtain B;
[0123] S3: Take 3 parts of polyvinyl alcohol and place them in 30 parts of distilled water, stir them evenly at room temperature, and then quickly heat them to 90-95°C to dissolve them quickly to obtain C;
[0124] S4: Add the products obtained from S2 and S3 to the product obtained from S1 which is stirred at a constant speed of 520 r / min, stir at room temperature for 205 min, and freeze-dry the product after stirring;
[0125] S5: During the high-temperature carbonization process of the freeze-dried product of S3, nitrogen was continuously introduced at a rate of 28 mL / min, the temperature was increased from room temperature to 350°C at a rate of 3°C / min, and the temperature was kept at 350°C for 60 minutes. Then, the temperature was increased from 350°C to 800°C at a rate of 5°C / min. After keeping at 800°C for 120 minutes, the temperature was decreased to 500°C at a rate of 5°C / min, and finally the temperature was naturally decreased from 500°C to room temperature to obtain a black semi-finished product. The black semi-finished product was filtered and washed with distilled water for 3 times, and then dried to obtain an oxygen-sulfur doped porous carbon material.
[0126] Comparative Example 5
[0127] S1: 3 parts of corn straw powder and 1.8 parts of a mixed alkali of KOH and NaOH in a mass ratio of 1:1 were mixed and ball-milled (ball milling speed of 650 rpm, ball milling for 20 minutes and pause for 10 minutes, repeated four times), and then placed in a mixed solvent of 90 parts of ethanol and water (ethanol and water volume ratio of 1:1) at room temperature and stirred for 3 hours to obtain A;
[0128] S2: 2.7 parts of sulfur, 2.7 parts of 1,3-propylenediamine, and 4.5 parts of polyvinyl chloride are placed in 63 parts of distilled water and mixed to obtain B;
[0129] S3: Take 3 parts of polyvinyl alcohol and place them in 30 parts of distilled water, stir them evenly at room temperature, and then quickly heat them to 90-95°C to dissolve them quickly to obtain C;
[0130] S4: The solution obtained in S3 is quickly added to the product obtained in S1 which is stirred at a constant speed of 520 r / min, and stirred at room temperature for 25 min. Then, the product B obtained in S2 is added thereto and stirred at room temperature for 3 hours. After the stirring is completed, the product is freeze-dried;
[0131] S5: During the high-temperature carbonization treatment of the freeze-dried product of S4, nitrogen was continuously introduced at a rate of 28 mL / min, the temperature was increased from room temperature to 350°C at a rate of 3°C / min, and the temperature was kept at 350°C for 60 minutes. The temperature was then increased from 350°C to 800°C at a rate of 5°C / min. After keeping at 800°C for 120 minutes, the temperature was then decreased to 500°C at a rate of 5°C / min. Finally, the temperature was naturally decreased from 500°C to room temperature to obtain a black semi-finished product. The black semi-finished product was filtered and washed with distilled water for 3 times, and then dried to obtain an oxygen-sulfur doped porous carbon material.
[0132] Comparative Example 6
[0133] S1: 3 parts of corn straw powder and 1.8 parts of a mixed alkali of KOH and NaOH in a mass ratio of 1:1 were mixed and ball-milled (ball milling speed of 650 rpm, ball milling for 20 minutes and pause for 10 minutes, repeated four times), and then placed in a mixed solvent of 90 parts of ethanol and water (ethanol and water volume ratio of 1:1) at room temperature and stirred for 3 hours to obtain A;
[0134] S2: 2.7 parts of sulfur, 2.7 parts of n-propylamine, and 4.5 parts of polyvinyl chloride were placed in 63 parts of distilled water and heated under reflux at 50°C with stirring for 7 hours to obtain B;
[0135] S3: Take 3 parts of polyvinyl alcohol and place them in 30 parts of distilled water, stir them evenly at room temperature, and then quickly heat them to 90-95°C to dissolve them quickly to obtain C;
[0136] S4: The solution obtained in S3 is quickly added to the product obtained in S1 which is stirred at a constant speed of 520 r / min, and stirred at room temperature for 25 min. Then, the product obtained in S2 is added thereto and stirred at room temperature for 3 hours. After the stirring is completed, the product is freeze-dried;
[0137] S5: During the high-temperature carbonization treatment of the freeze-dried product of S4, nitrogen was continuously introduced at a rate of 28 mL / min, the temperature was increased from room temperature to 350°C at a rate of 3°C / min, and the temperature was kept at 350°C for 60 minutes. The temperature was then increased from 350°C to 800°C at a rate of 5°C / min. After keeping at 800°C for 120 minutes, the temperature was then decreased to 500°C at a rate of 5°C / min. Finally, the temperature was naturally decreased from 500°C to room temperature to obtain a black semi-finished product. The black semi-finished product was filtered and washed with distilled water for 3 times, and then dried to obtain an oxygen-sulfur doped porous carbon material.
[0138] Comparative Example 7
[0139] S1: 3 parts of corn straw powder and 1.8 parts of a mixed alkali of KOH and NaOH in a mass ratio of 1:1 were mixed and ball-milled (ball milling speed of 650 rpm, ball milling for 20 minutes and pause for 10 minutes, repeated four times), and then placed in a mixed solvent of 90 parts of ethanol and water (ethanol and water volume ratio of 1:1) at room temperature and stirred for 3 hours to obtain A;
[0140] S2: 2.7 parts of sulfur, 2.7 parts of 1,3-propylenediamine, and 4.5 parts of polyethylene were placed in 63 parts of distilled water and heated under reflux at 50°C for 7 hours to obtain B;
[0141] S3: Take 3 parts of polyvinyl alcohol and place them in 30 parts of distilled water, stir them evenly at room temperature, and then quickly heat them to 90-95°C to dissolve them quickly to obtain C;
[0142] S4: The solution obtained in S3 is quickly added to the product obtained in S1 which is stirred at a constant speed of 520 r / min, and stirred at room temperature for 25 min. Then, the product obtained in S2 is added thereto and stirred at room temperature for 3 hours. After the stirring is completed, the product is freeze-dried;
[0143] S5: During the high-temperature carbonization treatment of the freeze-dried product of S4, nitrogen was continuously introduced at a rate of 28 mL / min, the temperature was increased from room temperature to 350°C at a rate of 3°C / min, and the temperature was kept at 350°C for 60 minutes. The temperature was then increased from 350°C to 800°C at a rate of 5°C / min. After keeping at 800°C for 120 minutes, the temperature was then decreased to 500°C at a rate of 5°C / min. Finally, the temperature was naturally decreased from 500°C to room temperature to obtain a black semi-finished product. The black semi-finished product was filtered and washed with distilled water for 3 times, and then dried to obtain an oxygen-sulfur doped porous carbon material.
[0144] Comparative Example 8
[0145] S1: 3 parts of corn straw powder and 1.8 parts of a mixed alkali of KOH and NaOH in a mass ratio of 1:1 were mixed and ball-milled (ball milling speed of 650 rpm, ball milling for 20 minutes and pause for 10 minutes, repeated four times), and then placed in a mixed solvent of 90 parts of ethanol and water (ethanol and water volume ratio of 1:1) at room temperature and stirred for 3 hours to obtain A;
[0146] S2: 2.7 parts of sulfur, 2.7 parts of 1,3-propylenediamine, and 4.5 parts of polyvinyl chloride were placed in 63 parts of distilled water and heated under reflux at 50°C for 7 hours. After the reaction was completed, the mixture was cooled to room temperature and filtered and dried to obtain B;
[0147] S3: Take 3 parts of polyvinyl alcohol and place them in 30 parts of distilled water, stir them evenly at room temperature, and then quickly heat them to 90-95°C to dissolve them quickly to obtain C;
[0148] S4: The solution obtained in S3 was quickly added to the product obtained in S1 which was stirred at a constant speed of 520 r / min, and stirred at room temperature for 205 min. After the stirring was completed, the product was freeze-dried;
[0149] S5: During the high-temperature carbonization treatment of the freeze-dried product of S4, nitrogen was continuously introduced at a rate of 28 mL / min, the temperature was increased from room temperature to 350°C at a rate of 3°C / min, and the temperature was kept at 350°C for 60 minutes. The temperature was then increased from 350°C to 800°C at a rate of 5°C / min. After keeping at 800°C for 120 minutes, the temperature was then decreased to 500°C at a rate of 5°C / min. Finally, the temperature was naturally decreased from 500°C to room temperature to obtain a black semi-finished product. The black semi-finished product was filtered and washed with distilled water for 3 times, and the carbon material was obtained after drying.
[0150] Comparative Example 9
[0151] S1: 3 parts of corn straw powder and 1.8 parts of a mixed alkali of KOH and NaOH in a mass ratio of 1:1 were mixed and ball-milled (ball milling speed of 650 rpm, ball milling for 20 minutes and pause for 10 minutes, repeated four times), and then placed in a mixed solvent of 90 parts of ethanol and water (ethanol and water volume ratio of 1:1) at room temperature and stirred for 3 hours to obtain A;
[0152] S2: 2.7 parts of sulfur, 2.7 parts of 1,3-propylenediamine, and 4.5 parts of polyvinyl chloride were placed in 63 parts of distilled water and heated under reflux at 50°C for 7 hours to obtain B;
[0153] S3: Take 1.5 parts of polyvinyl alcohol and place it in 30 parts of distilled water, stir it evenly at room temperature, and then quickly heat it to 90-95°C to dissolve it quickly to obtain C;
[0154] S4: The solution obtained in S3 is quickly added to the product obtained in S1 which is stirred at a constant speed of 520 r / min, and stirred at room temperature for 25 min. Then, the product obtained in S2 is added thereto and stirred at room temperature for 3 hours. After the stirring is completed, the product is freeze-dried;
[0155] S5: During the high-temperature carbonization treatment of the freeze-dried product of S4, nitrogen was continuously introduced at a rate of 28 mL / min, the temperature was increased from room temperature to 350°C at a rate of 3°C / min, and the temperature was kept at 350°C for 60 minutes. The temperature was then increased from 350°C to 800°C at a rate of 5°C / min. After keeping at 800°C for 120 minutes, the temperature was then decreased to 500°C at a rate of 5°C / min. Finally, the temperature was naturally decreased from 500°C to room temperature to obtain a black semi-finished product. The black semi-finished product was filtered and washed with distilled water for 3 times, and then dried to obtain an oxygen-sulfur doped porous carbon material.
[0156] Comparative Example 10
[0157] S1: 3 parts of corn straw powder and 1.8 parts of a mixed alkali of KOH and NaOH in a mass ratio of 1:1 were mixed and ball-milled (ball milling speed of 650 rpm, ball milling for 20 minutes and pause for 10 minutes, repeated four times), and then placed in a mixed solvent of 90 parts of ethanol and water (ethanol and water volume ratio of 1:1) at room temperature and stirred for 3 hours to obtain A;
[0158] S2: 2.7 parts of sulfur, 2.7 parts of 1,3-propylenediamine, and 4.5 parts of polyvinyl chloride were placed in 63 parts of distilled water and heated under reflux at 50°C for 7 hours to obtain B;
[0159] S3: Take 4.5 parts of polyvinyl alcohol and place it in 30 parts of distilled water, stir it evenly at room temperature, and then quickly heat it to 90-95°C to dissolve it quickly to obtain C;
[0160] S4: The solution obtained in S3 is quickly added to the product obtained in S1 which is stirred at a constant speed of 520 r / min, and stirred at room temperature for 25 min. Then, the product obtained in S2 is added thereto and stirred at room temperature for 3 hours. After the stirring is completed, the product is freeze-dried;
[0161] S5: During the high-temperature carbonization treatment of the freeze-dried product of S4, nitrogen was continuously introduced at a rate of 28 mL / min, the temperature was increased from room temperature to 350°C at a rate of 3°C / min, and the temperature was kept at 350°C for 60 minutes. The temperature was then increased from 350°C to 800°C at a rate of 5°C / min. After keeping at 800°C for 120 minutes, the temperature was then decreased to 500°C at a rate of 5°C / min. Finally, the temperature was naturally decreased from 500°C to room temperature to obtain a black semi-finished product. The black semi-finished product was filtered and washed with distilled water for 3 times, and then dried to obtain an oxygen-sulfur doped porous carbon material.
[0162] Comparative Example 11
[0163] S1: 3 parts of corn straw powder and 1.8 parts of a mixed alkali of KOH and NaOH in a mass ratio of 1:1 were mixed and ball-milled (ball milling speed of 650 rpm, ball milling for 20 minutes and pause for 10 minutes, repeated four times), and then placed in a mixed solvent of 90 parts of ethanol and water (ethanol and water volume ratio of 1:1) at room temperature and stirred for 3 hours to obtain A;
[0164] S2: 4.5 parts of sulfur, 4.5 parts of 1,3-propylenediamine, and 7.5 parts of polyvinyl chloride were placed in 100 parts of distilled water and heated under reflux at 50°C with stirring for 7 hours to obtain B;
[0165] S3: Take 3 parts of polyvinyl alcohol and place them in 30 parts of distilled water, stir them evenly at room temperature, and then quickly heat them to 90-95°C to dissolve them quickly to obtain C;
[0166] S4: The solution obtained in S3 is quickly added to the product obtained in S1 which is stirred at a constant speed of 520 r / min, and stirred at room temperature for 25 min. Then, the product obtained in S2 is added thereto and stirred at room temperature for 3 hours. After the stirring is completed, the product is freeze-dried;
[0167] S5: During the high-temperature carbonization treatment of the freeze-dried product of S4, nitrogen was continuously introduced at a rate of 28 mL / min, the temperature was increased from room temperature to 350°C at a rate of 3°C / min, and the temperature was kept at 350°C for 60 minutes. The temperature was then increased from 350°C to 800°C at a rate of 5°C / min. After keeping at 800°C for 120 minutes, the temperature was then decreased to 500°C at a rate of 5°C / min. Finally, the temperature was naturally decreased from 500°C to room temperature to obtain a black semi-finished product. The black semi-finished product was filtered and washed with distilled water for 3 times, and then dried to obtain an oxygen-sulfur doped porous carbon material.
[0168] Comparative Example 12
[0169] S1: 3 parts of corn stalk powder and 3 parts of a mixed alkali of KOH and NaOH in a mass ratio of 1:1 were mixed and ball-milled (ball milling speed was 650 rpm, ball milling was stopped for 10 minutes after 20 minutes, and repeated four times), and then placed in a mixed solvent of 90 parts of ethanol and water (ethanol and water volume ratio was 1:1) and stirred at room temperature for 3 hours to obtain A;
[0170] S2: 2.7 parts of sulfur, 2.7 parts of 1,3-propylenediamine, and 4.5 parts of polyvinyl chloride were placed in 63 parts of distilled water and heated under reflux at 50°C for 7 hours to obtain B;
[0171] S3: Take 3 parts of polyvinyl alcohol and place them in 30 parts of distilled water, stir them evenly at room temperature, and then quickly heat them to 90-95°C to dissolve them quickly to obtain C;
[0172] S4: The solution obtained in S3 is quickly added to the product obtained in S1 which is stirred at a constant speed of 520 r / min, and stirred at room temperature for 25 min. Then, the product obtained in S2 is added thereto and stirred at room temperature for 3 hours. After the stirring is completed, the product is freeze-dried;
[0173] S5: During the high-temperature carbonization treatment of the freeze-dried product of S4, nitrogen was continuously introduced at a rate of 28 mL / min, the temperature was increased from room temperature to 350°C at a rate of 3°C / min, and the temperature was kept at 350°C for 60 minutes. The temperature was then increased from 350°C to 800°C at a rate of 5°C / min. After keeping at 800°C for 120 minutes, the temperature was then decreased to 500°C at a rate of 5°C / min. Finally, the temperature was naturally decreased from 500°C to room temperature to obtain a black semi-finished product. The black semi-finished product was filtered and washed with distilled water for 3 times, and then dried to obtain an oxygen-sulfur doped porous carbon material.
[0174] Comparative Example 13
[0175] S1: 3 parts of corn straw powder and 1 part of a mixed alkali of KOH and NaOH in a mass ratio of 1:1 were mixed and ball-milled (ball milling speed was 650 rpm, ball milling was stopped for 10 minutes after 20 minutes, and repeated four times), and then placed in a mixed solvent of 90 parts of ethanol and water (ethanol and water volume ratio was 1:1) and stirred at room temperature for 3 hours to obtain A;
[0176] S2: 2.7 parts of sulfur, 2.7 parts of 1,3-propylenediamine, and 4.5 parts of polyvinyl chloride were placed in 63 parts of distilled water and heated under reflux at 50°C for 7 hours to obtain B;
[0177] S3: Take 3 parts of polyvinyl alcohol and place them in 30 parts of distilled water, stir them evenly at room temperature, and then quickly heat them to 90-95°C to dissolve them quickly to obtain C;
[0178] S4: The solution obtained in S3 is quickly added to the product obtained in S1 which is stirred at a constant speed of 520 r / min, and stirred at room temperature for 25 min. Then, the product obtained in S2 is added thereto and stirred at room temperature for 3 hours. After the stirring is completed, the product is freeze-dried;
[0179] S5: During the high-temperature carbonization treatment of the freeze-dried product of S4, nitrogen was continuously introduced at a rate of 28 mL / min, the temperature was increased from room temperature to 350°C at a rate of 3°C / min, and the temperature was kept at 350°C for 60 minutes. The temperature was then increased from 350°C to 800°C at a rate of 5°C / min. After keeping at 800°C for 120 minutes, the temperature was then decreased to 500°C at a rate of 5°C / min. Finally, the temperature was naturally decreased from 500°C to room temperature to obtain a black semi-finished product. The black semi-finished product was filtered and washed with distilled water for 3 times, and then dried to obtain an oxygen-sulfur doped porous carbon material.
[0180] Comparative Example 14
[0181] S1: 3 parts of corn straw powder and 1.8 parts of a mixed alkali of KOH and NaOH in a mass ratio of 1:1 were mixed and ball-milled (ball milling speed of 650 rpm, ball milling for 20 minutes and pause for 10 minutes, repeated four times), and then placed in a mixed solvent of 90 parts of ethanol and water (ethanol and water volume ratio of 1:1) at room temperature and stirred for 3 hours to obtain A;
[0182] S2: 2.7 parts of sulfur, 2.7 parts of 1,3-propylenediamine, and 2 parts of polyvinyl chloride were placed in 63 parts of distilled water and heated under reflux at 50°C with stirring for 7 hours to obtain B;
[0183] S3: Take 3 parts of polyvinyl alcohol and place them in 30 parts of distilled water, stir them evenly at room temperature, and then quickly heat them to 90-95°C to dissolve them quickly to obtain C;
[0184] S4: The solution obtained in S3 is quickly added to the product obtained in S1 which is stirred at a constant speed of 520 r / min, and stirred at room temperature for 25 min. Then, the product obtained in S2 is added thereto and stirred at room temperature for 3 hours. After the stirring is completed, the product is freeze-dried;
[0185] S5: During the high-temperature carbonization treatment of the freeze-dried product of S4, nitrogen was continuously introduced at a rate of 28 mL / min, the temperature was increased from room temperature to 350°C at a rate of 3°C / min, and the temperature was kept at 350°C for 60 minutes. The temperature was then increased from 350°C to 800°C at a rate of 5°C / min. After keeping at 800°C for 120 minutes, the temperature was then decreased to 500°C at a rate of 5°C / min. Finally, the temperature was naturally decreased from 500°C to room temperature to obtain a black semi-finished product. The black semi-finished product was filtered and washed with distilled water for 3 times, and then dried to obtain an oxygen-sulfur doped porous carbon material.
[0186] Comparative Example 15
[0187] S1: 3 parts of corn straw powder and 1.8 parts of a mixed alkali of KOH and NaOH in a mass ratio of 1:1 were mixed and ball-milled (ball milling speed of 650 rpm, ball milling for 20 minutes and pause for 10 minutes, repeated four times), and then placed in a mixed solvent of 90 parts of ethanol and water (ethanol and water volume ratio of 1:1) at room temperature and stirred for 3 hours to obtain A;
[0188] S2: 2.7 parts of sulfur, 1 part of 1,3-propylenediamine, and 4.5 parts of polyvinyl chloride were placed in 63 parts of distilled water and heated under reflux at 50°C with stirring for 7 hours to obtain B;
[0189] S3: Take 3 parts of polyvinyl alcohol and place them in 30 parts of distilled water, stir them evenly at room temperature, and then quickly heat them to 90-95°C to dissolve them quickly to obtain C;
[0190] S4: The solution obtained in S3 is quickly added to the product obtained in S1 which is stirred at a constant speed of 520 r / min, and stirred at room temperature for 25 min. Then, the product obtained in S2 is added thereto and stirred at room temperature for 3 hours. After the stirring is completed, the product is freeze-dried;
[0191] S5: During the high-temperature carbonization treatment of the freeze-dried product of S4, nitrogen was continuously introduced at a rate of 28 mL / min, the temperature was increased from room temperature to 350°C at a rate of 3°C / min, and the temperature was kept at 350°C for 60 minutes. The temperature was then increased from 350°C to 800°C at a rate of 5°C / min. After keeping at 800°C for 120 minutes, the temperature was then decreased to 500°C at a rate of 5°C / min. Finally, the temperature was naturally decreased from 500°C to room temperature to obtain a black semi-finished product. The black semi-finished product was filtered and washed with distilled water for 3 times, and then dried to obtain an oxygen-sulfur doped porous carbon material.
[0192] Comparative Example 16
[0193] S1: 3 parts of corn straw powder and 1.8 parts of a mixed alkali of KOH and NaOH in a mass ratio of 1:1 were mixed and ball-milled (ball milling speed of 650 rpm, ball milling for 20 minutes and pause for 10 minutes, repeated four times), and then placed in a mixed solvent of 90 parts of ethanol and water (ethanol and water volume ratio of 1:1) at room temperature and stirred for 3 hours to obtain A;
[0194] S2: 1.5 parts of sulfur, 2.7 parts of 1,3-propylenediamine, and 4.5 parts of polyvinyl chloride were placed in 63 parts of distilled water and heated under reflux at 50°C for 7 hours to obtain B;
[0195] S3: Take 3 parts of polyvinyl alcohol and place them in 30 parts of distilled water, stir them evenly at room temperature, and then quickly heat them to 90-95°C to dissolve them quickly to obtain C;
[0196] S4: The solution obtained in S3 is quickly added to the product obtained in S1 which is stirred at a constant speed of 520 r / min, and stirred at room temperature for 25 min. Then, the product obtained in S2 is added thereto and stirred at room temperature for 3 hours. After the stirring is completed, the product is freeze-dried;
[0197] S5: During the high-temperature carbonization treatment of the freeze-dried product of S4, nitrogen was continuously introduced at a rate of 28 mL / min, the temperature was increased from room temperature to 350°C at a rate of 3°C / min, and the temperature was kept at 350°C for 60 minutes. The temperature was then increased from 350°C to 800°C at a rate of 5°C / min. After keeping at 800°C for 120 minutes, the temperature was then decreased to 500°C at a rate of 5°C / min. Finally, the temperature was naturally decreased from 500°C to room temperature to obtain a black semi-finished product. The black semi-finished product was filtered and washed with distilled water for 3 times, and then dried to obtain an oxygen-sulfur doped porous carbon material.
[0198] Comparative Example 17
[0199] S1: 3 parts of corn straw powder and 1.8 parts of a mixed alkali of KOH and NaOH in a mass ratio of 1:1 were mixed and ball-milled (ball milling speed of 650 rpm, ball milling for 20 minutes and pause for 10 minutes, repeated four times), and then placed in a mixed solvent of 90 parts of ethanol and water (ethanol and water volume ratio of 1:1) at room temperature and stirred for 3 hours to obtain A;
[0200] S2: 2.7 parts of sulfur, 2.7 parts of 1,3-propylenediamine, and 4.5 parts of polyvinyl chloride were placed in 63 parts of distilled water and heated under reflux at 50°C for 7 hours to obtain B;
[0201] S3: Take 3 parts of polyvinyl alcohol and place them in 30 parts of distilled water, stir them evenly at room temperature, and then quickly heat them to 90-95°C to dissolve them quickly to obtain C;
[0202] S4: The solution obtained in S3 is quickly added to the product obtained in S1 which is stirred at a constant speed of 520 r / min, and stirred at room temperature for 25 min. Then, the product obtained in S2 is added thereto and stirred at room temperature for 1 hour. After the stirring is completed, the product is freeze-dried;
[0203] S5: During the high-temperature carbonization treatment of the freeze-dried product of S4, nitrogen was continuously introduced at a rate of 28 mL / min, the temperature was increased from room temperature to 350°C at a rate of 3°C / min, and the temperature was kept at 350°C for 60 minutes. The temperature was then increased from 350°C to 800°C at a rate of 5°C / min. After keeping at 800°C for 120 minutes, the temperature was then decreased to 500°C at a rate of 5°C / min. Finally, the temperature was naturally decreased from 500°C to room temperature to obtain a black semi-finished product. The black semi-finished product was filtered and washed with distilled water for 3 times, and then dried to obtain an oxygen-sulfur doped porous carbon material.
[0204] Comparative Example 18
[0205] S1: 3 parts of corn straw powder and 1.8 parts of a mixed alkali of KOH and NaOH in a mass ratio of 1:1 were mixed and ball-milled (ball milling speed of 650 rpm, ball milling for 20 minutes and pause for 10 minutes, repeated four times), and then placed in a mixed solvent of 90 parts of ethanol and water (ethanol and water volume ratio of 1:1) at room temperature and stirred for 3 hours to obtain A;
[0206] S2: 2.7 parts of sulfur, 2.7 parts of 1,3-propylenediamine, and 4.5 parts of polyvinyl chloride were placed in 63 parts of distilled water and heated under reflux at 50°C for 7 hours to obtain B;
[0207] S3: Take 3 parts of polyvinyl alcohol and place them in 30 parts of distilled water, stir them evenly at room temperature, and then quickly heat them to 90-95°C to dissolve them quickly to obtain C;
[0208] S4: The solution obtained in S3 is quickly added to the product obtained in S1 which is stirred at a constant speed of 520 r / min, and stirred at room temperature for 25 min. Then, the product obtained in S2 is added thereto and stirred at room temperature for 5 hours. After the stirring is completed, the product is freeze-dried;
[0209] S5: During the high-temperature carbonization treatment of the freeze-dried product of S4, nitrogen was continuously introduced at a rate of 28 mL / min, the temperature was increased from room temperature to 350°C at a rate of 3°C / min, and the temperature was kept at 350°C for 60 minutes. The temperature was then increased from 350°C to 800°C at a rate of 5°C / min. After keeping at 800°C for 120 minutes, the temperature was then decreased to 500°C at a rate of 5°C / min. Finally, the temperature was naturally decreased from 500°C to room temperature to obtain a black semi-finished product. The black semi-finished product was filtered and washed with distilled water for 3 times, and then dried to obtain an oxygen-sulfur doped porous carbon material.
[0210] Comparative Example 19
[0211] S1: 3 parts of corn straw powder and 1.8 parts of a mixed alkali of KOH and NaOH in a mass ratio of 1:1 were mixed and ball-milled (ball milling speed of 650 rpm, ball milling for 20 minutes and pause for 10 minutes, repeated four times), and then placed in a mixed solvent of 90 parts of ethanol and water (ethanol and water volume ratio of 1:1) at room temperature and stirred for 3 hours to obtain A;
[0212] S2: 2.7 parts of sulfur, 2.7 parts of 1,3-propylenediamine, and 4.5 parts of polyvinyl chloride were placed in 63 parts of distilled water and heated under reflux at 50°C for 7 hours to obtain B;
[0213] S3: Take 3 parts of polyvinyl alcohol and place them in 30 parts of distilled water, stir them evenly at room temperature, and then quickly heat them to 90-95°C to dissolve them quickly to obtain C;
[0214] S4: The solution obtained in S3 is quickly added to the product obtained in S1 which is stirred at a constant speed of 520 r / min, and stirred at room temperature for 25 min. Then, the product obtained in S2 is added thereto and stirred at room temperature for 3 hours. After the stirring is completed, the product is freeze-dried;
[0215] S5: The freeze-dried product of S4 was subjected to high-temperature carbonization treatment, and nitrogen was continuously introduced at a rate of 28 mL / min. The temperature was increased from room temperature to 350°C at a rate of 3°C / min, and kept at 350°C for 60 minutes. The temperature was then increased from 350°C to 550°C at a rate of 5°C / min. After keeping at 550°C for 120 minutes, the temperature was then decreased to 500°C at a rate of 5°C / min. Finally, the temperature was naturally decreased from 500°C to room temperature to obtain a black semi-finished product. The black semi-finished product was filtered and washed with distilled water for 3 times, and then dried to obtain an oxygen-sulfur doped porous carbon material.
[0216] Comparative Example 20
[0217] S1: 3 parts of corn straw powder and 1.8 parts of a mixed alkali of KOH and NaOH in a mass ratio of 1:1 were mixed and ball-milled (ball milling speed of 650 rpm, ball milling for 20 minutes and pause for 10 minutes, repeated four times), and then placed in a mixed solvent of 90 parts of ethanol and water (ethanol and water volume ratio of 1:1) at room temperature and stirred for 3 hours to obtain A;
[0218] S2: 2.7 parts of sulfur, 2.7 parts of 1,3-propylenediamine, and 4.5 parts of polyvinyl chloride were placed in 63 parts of distilled water and heated under reflux at 50°C for 7 hours to obtain B;
[0219] S3: Take 3 parts of polyvinyl alcohol and place them in 30 parts of distilled water, stir them evenly at room temperature, and then quickly heat them to 90-95°C to dissolve them quickly to obtain C;
[0220] S4: The solution obtained in S3 is quickly added to the product obtained in S1 which is stirred at a constant speed of 520 r / min, and stirred at room temperature for 25 min. Then, the product obtained in S2 is added thereto and stirred at room temperature for 3 hours. After the stirring is completed, the product is freeze-dried;
[0221] S5: During the high-temperature carbonization treatment of the freeze-dried product of S4, nitrogen was continuously introduced at a rate of 28 mL / min, the temperature was increased from room temperature to 350°C at a rate of 3°C / min, and the temperature was kept at 350°C for 60 minutes. The temperature was then increased from 350°C to 1050°C at a rate of 5°C / min. After keeping at 1050°C for 120 minutes, the temperature was then decreased to 500°C at a rate of 5°C / min. Finally, the temperature was naturally decreased from 500°C to room temperature to obtain a black semi-finished product. The black semi-finished product was filtered and washed with distilled water for 3 times, and then dried to obtain an oxygen-sulfur doped porous carbon material.
[0222] Effect example
[0223] The carbon materials prepared in Examples 1-9 and Comparative Examples 1-20 were used to prepare rubber waterstops by the following method, wherein:
[0224] Natural rubber was purchased from Hubei Jusheng Technology Co., Ltd.;
[0225] Zinc oxide was purchased from Jinan Huiteng Chemical Co., Ltd.;
[0226] Stearic acid was purchased from Nanjing Huaxi Chemical Co., Ltd.;
[0227] Petroleum resin was purchased from Shandong Maofa Chemical Co., Ltd.;
[0228] DM was purchased from Guangzhou Dongxin Chemical Co., Ltd.;
[0229] DZ was purchased from Guangzhou Dongxin Chemical Co., Ltd.;
[0230] FD170 was purchased from Guangzhou Dongxin Chemical Co., Ltd.
[0231] Effect Example 1
[0232] The material parts used in this effect example are as follows: 100 parts of natural rubber, 30 parts of the carbon material obtained in Example 1 as a reinforcing agent, 6 parts of an activator (zinc oxide), 1 part of stearic acid, 17 parts of a softener (petroleum resin), 3 parts of an antioxidant (DM), 2 parts of an accelerator (CZ), and 25 parts of a filler (FD170).
[0233] S1: Plasticizing
[0234] Set the initial temperature of the internal mixer to 70℃ and the speed to 40 rpm, cut the natural rubber into small pieces and add them into the internal mixer, plasticate for 6 minutes, and discharge when the temperature of the internal mixer reaches 100℃. Pass it on the open mixer, make triangle bags 4 times, and leave it for at least 8 hours before use.
[0235] S2: One-stage mixing
[0236] Set the initial temperature of the internal mixer to 85℃ and the speed to 35 rpm. Add the plasticized natural rubber to the internal mixer. After about 45 seconds, lift the top plug to add reinforcing agent, filler, activator, stearic acid, softener and antioxidant, press the top plug, mix for 160 seconds, lift the plug once in the middle, and discharge the rubber at a temperature of 110℃. After a section of mixed rubber falls into the open mixer, adjust the roller distance to 5mm, automatically pour the rubber 4 times, and the roller temperature of the open mixer does not exceed 60℃. After pouring the rubber, unload the sheet and leave it for at least 8 hours before use.
[0237] S3: Second stage mixing
[0238] Set the initial temperature of the internal mixer to 85°C and the speed to 35 rpm. Fill the first-stage mixed rubber into the internal mixer. After pressurizing for 45 seconds, lift the top plug and add the accelerator. Press the top plug and mix for 80 seconds. The mixing temperature is 110°C and the rubber is discharged. After the second-stage mixed rubber falls into the open mixer, adjust the roller distance to 5mm, and automatically pour the rubber 4 times. The roller temperature of the open mixer does not exceed 60°C. After the pouring is completed, unload the sheet and leave it for at least 8 hours before use to obtain sample 1.
[0239] Effect Example 2
[0240] The preparation method of this effect example is the same as that of effect example 1, the only difference being that the carbon material used is the one obtained in Example 2, and sample 2 is obtained.
[0241] Effect Example 3
[0242] The preparation method of this effect example is the same as that of effect example 1, the only difference being that the carbon material used is the one obtained in Example 3, and sample 3 is obtained.
[0243] Effect Example 4
[0244] The preparation method of this effect example is the same as that of effect example 1, the only difference being that the carbon material used is the one obtained in Example 4, and sample 4 is obtained.
[0245] Effect Example 5
[0246] The preparation method of this effect example is the same as that of effect example 1, the only difference being that the carbon material used is the one obtained in Example 5, and sample 5 is obtained.
[0247] Effect Example 6
[0248] The preparation method of this effect example is the same as that of effect example 1, the only difference being that the carbon material used is that obtained in Example 6, and sample 6 is obtained.
[0249] Effect Example 7
[0250] The preparation method of this effect example is the same as that of effect example 1, the only difference being that the carbon material used is that obtained in Example 7, and sample 7 is obtained.
[0251] Effect Example 8
[0252] The preparation method of this effect example is the same as that of effect example 1, the only difference being that the carbon material used is that obtained in Example 8, and sample 8 is obtained.
[0253] Effect Example 9
[0254] The preparation method of this effect example is the same as that of effect example 1, the only difference being that the carbon material used is obtained from Example 9, and sample 9 is obtained.
[0255] Effect Example 10
[0256] The preparation method of this effect example is the same as that of effect example 1, the only difference being that the carbon material used is the one obtained in comparative example 1, and sample 10 is obtained.
[0257] Effect Example 11
[0258] The preparation method of this effect example is the same as that of effect example 1, the only difference being that the carbon material used is the one obtained in comparative example 2, and sample 11 is obtained.
[0259] Effect Example 12
[0260] The preparation method of this effect example is the same as that of effect example 1, the only difference being that the carbon material used is the one obtained in comparative example 3, and sample 12 is obtained.
[0261] Effect Example 13
[0262] The preparation method of this effect example is the same as that of effect example 1, the only difference being that the carbon material used is the one obtained in comparative example 4, and sample 13 is obtained.
[0263] Effect Example 14
[0264] The preparation method of this effect example is the same as that of effect example 1, the only difference being that the carbon material used is the one obtained in comparative example 5, and sample 14 is obtained.
[0265] Effect Example 15
[0266] The preparation method of this effect example is the same as that of effect example 1, the only difference being that the carbon material used is the one obtained in comparative example 6, and sample 15 is obtained.
[0267] Effect Example 16
[0268] The preparation method of this effect example is the same as that of effect example 1, the only difference being that the carbon material used is the one obtained in comparative example 7, and sample 16 is obtained.
[0269] Effect Example 17
[0270] The preparation method of this effect example is the same as that of effect example 1, the only difference being that the reinforcing agent used is the carbon material obtained in comparative example 8 and the product B obtained in comparative example 8 in a mass ratio of 6:10, and sample 17 is obtained.
[0271] Effect Example 18
[0272] The preparation method of this effect example is the same as that of effect example 1, the only difference being that the carbon material used is the one obtained in comparative example 9, and sample 18 is obtained.
[0273] Effect Example 19
[0274] The preparation method of this effect example is the same as that of effect example 1, the only difference being that the carbon material used is the one obtained in comparative example 10, and sample 19 is obtained.
[0275] Effect Example 20
[0276] The preparation method of this effect example is the same as that of effect example 1, the only difference being that the carbon material used is the one obtained in comparative example 11, and sample 20 is obtained.
[0277] Effect Example 21
[0278] The preparation method of this effect example is the same as that of effect example 1, the only difference being that the carbon material used is the one obtained in comparative example 12, and sample 21 is obtained.
[0279] Effect Example 22
[0280] The preparation method of this effect example is the same as that of effect example 1, the only difference being that the carbon material used is the one obtained in comparative example 13, and sample 22 is obtained.
[0281] Effect Example 23
[0282] The preparation method of this effect example is the same as that of effect example 1, the only difference being that the carbon material used is the one obtained in comparative example 14, and sample 23 is obtained.
[0283] Effect Example 24
[0284] The preparation method of this effect example is the same as that of effect example 1, the only difference being that the carbon material used is the one obtained in comparative example 15, and sample 24 is obtained.
[0285] Effect Example 25
[0286] The preparation method of this effect example is the same as that of effect example 1, the only difference being that the carbon material used is the one obtained from comparative example 16, and sample 25 is obtained.
[0287] Effect Example 26
[0288] The preparation method of this effect example is the same as that of effect example 1, the only difference being that the carbon material used is obtained from comparative example 17, and sample 26 is obtained.
[0289] Effect Example 27
[0290] The preparation method of this effect example is the same as that of effect example 1, the only difference being that the carbon material used is the one obtained from comparative example 18, and sample 27 is obtained.
[0291] Effect Example 28
[0292] The preparation method of this effect example is the same as that of effect example 1, the only difference being that the carbon material used is the one obtained in comparative example 19, and sample 28 is obtained.
[0293] Effect Example 29
[0294] The preparation method of this effect example is the same as that of effect example 1, the only difference being that the carbon material used is obtained from comparative example 20, and sample 29 is obtained.
[0295] This experiment is based on the test of "Railway Tunnel Waterproof Materials Part 2: Waterstop" (TB / T 3360.2-2014). The performance data of "Railway Tunnel Waterproof Materials Part 2: Waterstop" (TB / T 3360.2-2014) are shown in Table 1 below.
[0296] Table 1
[0297]
[0298] The test was carried out in accordance with "Railway Tunnel Waterproof Materials Part 2: Waterstop" (TB / T 3360.2-2014), and the results are shown in Table 2 and Table 3 below.
[0299] Table 2
[0300]
[0301] Table 3
[0302]
[0303] Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art may still modify the technical solutions described in the aforementioned embodiments, or make equivalent substitutions for some of the technical features therein; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing an oxygen-sulfur-doped porous carbon material for a rubber waterstop reinforcement, characterized in that: It includes the following steps: S1: Mix the biomass material and the alkali ball mill, and place the ball-milled mixture into alcohol water and stir at room temperature for 2-4 hours; S2: Heat sulfur, aliphatic diamine and polyvinyl chloride in distilled water at 40-70°C and reflux with stirring for 6-8 hours; S3: Stir polyvinyl alcohol in water at room temperature and dissolve it quickly after heating; S4: quickly add the solution obtained in S3 to the product obtained in S1 which is stirred at a constant speed of 470-570 r / min, continue stirring at room temperature for 20-30 min, then add the product obtained in S2 and stir at room temperature for 2.5-3.5 hours. After stirring, freeze-dry the product; S5: carbonizing the freeze-dried product of S4 at 700-900° C. under a protective gas atmosphere, washing and filtering after cooling, to obtain an oxygen-sulfur doped porous carbon material; The biomass material is selected from one of corn straw powder, wheat straw powder and rice straw powder; The mass ratio of the biomass material to the alkali is 5:2.5-3.5; The mass ratio of sulfur, aliphatic diamine and polyvinyl chloride is 3:2.5-3.5:4-6; The mass ratio of the biomass material to sulfur is 1:0.8-1.2; The mass ratio of the biomass material to polyvinyl alcohol is 1:0.8-1.
2.
2. The method for preparing an oxygen-sulfur-doped porous carbon material for a rubber waterstop reinforcing agent according to claim 1, characterized in that: The alcohol water is a mixture of ethanol and water in a volume ratio of 1-2:2-1; The base is selected from any one or more of sodium hydroxide, potassium hydroxide, and sodium carbonate; The aliphatic diamine is selected from one of 1,3-propylenediamine, ethylenediamine and 1,2-propylenediamine; The protective gas is selected from one of nitrogen, helium and argon.
3. The method for preparing an oxygen-sulfur-doped porous carbon material for a rubber waterstop reinforcing agent according to claim 1, characterized in that: In step S1, the rotation speed of the ball mill is 600-700 r / min, the ball milling is performed for 15-25 min, and then the ball milling is paused for 5-10 min, and the process is repeated 3-5 times.
4. The method for preparing an oxygen-sulfur-doped porous carbon material for a rubber waterstop reinforcing agent according to claim 1, characterized in that: In the carbonization process in step S5, the protective gas is continuously introduced at a rate of 20-35 mL / min, the temperature is increased from room temperature to 300-400°C at a rate of 2-4°C / min, and the temperature is kept at 300-400°C for 40-80 minutes, and then the temperature is further increased to 700-900°C at a rate of 3-10°C / min. After being kept at 700-900°C for 60-180 minutes, the temperature is then reduced to 400-600°C at a rate of 3-10°C / min, and finally the temperature is naturally reduced from 400-600°C to room temperature.
5. The method for preparing an oxygen-sulfur-doped porous carbon material for a rubber waterstop reinforcing agent according to claim 1, characterized in that: The mass ratio of the biomass material to the alkali is 5:3; The mass ratio of sulfur, aliphatic diamine and polyvinyl chloride is 3:3:5, the heating reflux stirring time is 7 hours, and the temperature is 50°C; The biomass material is corn stalk powder; The alcohol water is a mixture of ethanol and water in a volume ratio of 1:1; The base is selected from sodium hydroxide and potassium hydroxide in a mass ratio of 1:1; The aliphatic diamine is selected from 1,3-propylenediamine; The mass ratio of the biomass material to the polyvinyl alcohol is 1:1; The mass ratio of the biomass material to sulfur is 1:0.
9.
6. The method for preparing an oxygen-sulfur-doped porous carbon material for a rubber waterstop reinforcing agent according to claim 1, characterized in that: In the step S1, the rotation speed of the ball mill is 650 rpm, the ball milling is performed for 20 min, and the ball milling is paused for 10 min, which is repeated 4 times.
7. The method for preparing an oxygen-sulfur-doped porous carbon material for a rubber waterstop reinforcing agent according to claim 1, characterized in that: In the carbonization process in step S5, protective gas is continuously introduced at a rate of 28 mL / min, the temperature is increased from room temperature to 350°C at a rate of 3°C / min, kept at 350°C for 60 minutes, then increased from 350°C to 800°C at a rate of 5°C / min, kept at 800°C for 120 minutes, then cooled to 500°C at a rate of 5°C / min, and finally cooled naturally from 500°C to room temperature.
8. An oxygen-sulfur-doped porous carbon material used as a rubber waterstop reinforcement obtained by the preparation method according to any one of claims 1 to 7.
9. Use of an oxygen-sulfur-doped porous carbon material for a rubber waterstop reinforcement obtained by the preparation method as described in any one of claims 1 to 7 in the field of rubber preparation.
10. The use according to claim 9, characterized in that: The application is the preparation of rubber waterstop.
Citation Information
Patent Citations
PVC composite material and preparation method thereof
CN107501814A
Wear-resistant pressure pipeline and preparation method thereof
CN113185783A
